A Competitive Approach to Financial Issues: Modern Finance Theory - (:unkn) unknown (IGI GLOBAL, 2014)
Efficient Market Hypothesis (EMH) is a cornerstone in modern finance theory. Efficient market hypothesis states that it is impossible to make abnormal returns in financial markets because financial asset prices always reflect all available information. This chapter was undertaken in order to give a brief survey of modern finance theory by mainly focusing on the efficient market hypothesis. The authors also discuss the empirical foundations of the efficient market hypothesis. Finally, the main challenges to the efficient market hypothesis are introduced in order to point out a perspective for future research.
Keywords: EFFICIENT; MARKETS